1990
DOI: 10.1080/07340669008251531
|View full text |Cite
|
Sign up to set email alerts
|

Slowness in elderly gait

Abstract: The aim of this research was to better understand how gait slows with age. We analyzed the kinematic parameters of locomotion (velocity, stride length, cycle duration, swing and double support durations), and their interrelationships both in the slowing process due to aging and in intentional modulations of velocity. The experiments were carried out on a group of 67 elderly adults (aged 60 to 80+) walking with a free gait and a fast gait. This group was compared to a young population in equivalent situations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
6

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 10 publications
6
50
0
6
Order By: Relevance
“…Slow walking speed in the elderly has been reported in many previous papers (Murray et al, 1969;Hageman and Blanke, 1986;Himann et al, 1988;Kaneko et al, 1991), and this slowness has been found to be mainly caused by short stride length (Imms and Edholm, 1981;Ferrandez et al, 1990;Nishizawa et al, 2000). Over the last century, differences in height have been observed between cohorts in developed countries (Kouchi, 1996).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Slow walking speed in the elderly has been reported in many previous papers (Murray et al, 1969;Hageman and Blanke, 1986;Himann et al, 1988;Kaneko et al, 1991), and this slowness has been found to be mainly caused by short stride length (Imms and Edholm, 1981;Ferrandez et al, 1990;Nishizawa et al, 2000). Over the last century, differences in height have been observed between cohorts in developed countries (Kouchi, 1996).…”
Section: Discussionmentioning
confidence: 87%
“…Long stance phase duration equates to a long double support phase. Long double support duration aids balance in bipedal walking (Ferrandez et al, 1990;Kimura et al, 2005), and can be an adaptive characteristic of the older elderly people in response to impaired balance. The relative stance phase duration was longer in the elderly than in the young adults, but the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modifications to the gait patterns among elderly people have not been completely clarified, but many studies on this subject have been published 7,[11][12][13] . One of the most consistent findings from these studies is that elderly people walk more slowly than young adults do [14][15][16] . This phenomenon has been interpreted by some authors as a compensatory strategy to ensure stability 17 .…”
Section: Introductionmentioning
confidence: 86%
“…It is well established that older adults tend to adopt a more conservative gait pattern as reflected in a decreased step or stride length, increased stride width, and slowed gait speed [49][50][51]. Indeed, there is a reduction of about 4% in step length between the ages of 20 and 60 years and a reduction of 6% between the ages of 60 and 70 years [52].…”
Section: Aging and The Time To Stability In Postural Controlmentioning
confidence: 99%